Hubungan Personal Hygiene, Sanitasi Lingkungan, dan Status Gizi Terhadap Infeksi Cacing Usus Di SDN 3 Pringgabaya Kabupaten Lombok Timur - Diah Kadek Sulistyawati; Aena Mardiah; Fahriana Azmi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Parasitic worm infections in the intestines remain a major public health concern among children, particularly in areas where hygiene practices and environmental cleanliness are still lacking. Primary school-aged children are more susceptible because they often come into direct contact with soil and tend to have suboptimal personal hygiene behaviors. These infections may disrupt the body’s ability to absorb nutrients and can adversely affect overall nutritional status. Several factors are thought to contribute to the risk of infection, including individual hygiene practices, environmental sanitation conditions, and nutritional status. This study was conducted to examine the relationship between personal hygiene, environmental sanitation, and nutritional status with the occurrence of intestinal helminth infections among students of SDN 3 Pringgabaya, East Lombok Regency. The research applied a cross-sectional approach and involved 37 respondents who met predetermined inclusion and exclusion criteria. Information on hygiene practices and environmental sanitation was collected using questionnaires. Nutritional status was assessed through anthropometric measurements based on Body Mass Index for Age (BMI-for-Age), while infection status was determined באמצעות microscopic examination of stool samples. The results indicated that 8 respondents (21.6%) were infected. Most participants demonstrated good personal hygiene (81.1%), adequate environmental sanitation (64.9%), and normal nutritional status (62.2%). Statistical analysis showed a significant relationship between personal hygiene (p=0.000) and environmental sanitation (p=0.001) with the incidence of infection, whereas nutritional status was not significantly associated (p=0.323). Therefore, improving hygiene practices and maintaining proper environmental sanitation are crucial preventive measures against intestinal helminth infections.